2004
DOI: 10.1007/s00405-003-0642-7
|View full text |Cite
|
Sign up to set email alerts
|

Videostroboscopic assessment of unilateral vocal fold paralysis after augmentation with autologous fascia

Abstract: Vocal fold augmentation by injection laryngoplasty is a simple and fast procedure. The aim of this prospective study was to assess the glottal closure and the travelling mucosal wave by videostroboscopic images after autologous fascia augmentation in unilateral vocal fold paralysis (UVFP) with a special reference to objective analysis of voice. A total of 14 UVFP patients with poor voice and open glottal gap were assessed by videostroboscopy, blinded perceptual evaluation of running speech and acoustical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a similar study by Reijonen et al, most voice parameters significantly improved after injection laryngoplasty with autologous fascia (13). In another study by Rihkanen et al, video analysis revealed fewer large glottal gaps after augmentation with autologous fascia (14). In addition, the maximum gap between the vocal folds decreased from 7.21 to 1.65 units.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a similar study by Reijonen et al, most voice parameters significantly improved after injection laryngoplasty with autologous fascia (13). In another study by Rihkanen et al, video analysis revealed fewer large glottal gaps after augmentation with autologous fascia (14). In addition, the maximum gap between the vocal folds decreased from 7.21 to 1.65 units.…”
Section: Discussionmentioning
confidence: 82%
“…Use of fascia lata can minimize the risk of rejection, allergic reactions, scarring or fibrosis of the subepithelial space, and infection transmission; moreover, it shows effective results on voice analysis (14,17,18). In a study on fascia augmentation of the vocal fold, the mean fascia graft yield in the canine larynx was 33%, which suggests that significant overcorrection may be necessary to produce optimal results; however, their clinical experience did not indicate these trends (17).…”
Section: Discussionmentioning
confidence: 99%
“…[2] Bruening performed the first injection augmentation of the vocal folds using paraffin in 1911. [3] Since then, several injectable substances have been used to treat glottal insufficiency, including fat, [4] fascia, [5] gel foam, [6] collagen, [7] silicone, [8] Teflon, [9] and others. [10] Each of these substances has demonstrated limitations such as poor long-term durability, migration from the injection site, inflammation, granuloma formation, and interference with vocal fold vibration due to viscoelastic mismatch [11][13].…”
Section: Introductionmentioning
confidence: 99%